The THE IMPLEMENTATION OF ARTICLE 66 ENVIRONMENTAL PROTECTION AND MANAGEMENT LAW OF STRATEGIC LEGAL ACTION AGAINST PUBLIC PARTICIPATION DUE TO CRIMINAL ACTS OF ENVIRONMENTAL DESTRUCTION AT STATE COURT - Sariroh, ST.; Ali, Mohammad (TAHKIM, 2024)
Environmental problems are increasingly diverse in all regions from small scale to serious large scale. Article 66 reporting on allegations of environmental pollution will be protected by the state. However, the current reality is that the victims are getting worse, deprived of rights and no legal protection by a party in the legal efforts taken. Researchers will examine more deeply the views of judges as law enforcers regarding the existence of Article 66. This empirical research used normative-descriptive, by describing the judges' opinions on the implementation of Article 66 on Strategic Legal Action Against Public Participation and analyzed with an Administrative Law Perspective. The study results indicate that the judge believes there are still few reports or lawsuits on environmental cases because Jember is not yet a large-scale industrial area. By law, article 66 is a form of protection that must be implemented properly. However, it must be careful and accommodate all existing values. Because the judiciary cannot reject every registered lawsuit.